1993
DOI: 10.1073/pnas.90.3.1018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the cardioprotective effect of transforming growth factor beta 1 in feline myocardial ischemia and reperfusion.

Abstract: We studied the effects of transforming growth factor Pi (TGF-f1) in a feline model of myocardial ischemia (1.5 hr) and reperfusion (4.5 hr). Myocardial ischenma followed by reperfusion resulted in severe myocardial imjury, endothelial dysfunction, high cardiac myeloperoxidase activity indicative of neutrophil accumulation in the ischemic myocardium, and sinicant neutrophil adherence to the ischemic coronary endothelium. In contrast, intravenous administration of TGF-Pi (20 pg/kg) 30 min prior to reperfusion si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 35 publications
3
57
2
2
Order By: Relevance
“…In a model of reperfused feline myocardial infarction, TGF-β1 administration reduced cardiomyocyte death; these protective actions were associated with attenuated neutrophil recruitment in the infarcted myocardium (47). Whether TGF-β-mediated protection in these studies is due to activation of direct pro-survival pathways in cardiomyocytes, or reflects suppression of injurious inflammatory signaling, remains unknown.…”
Section: Effects Of Tgf-β On Ischemic Cardiomyocytesmentioning
confidence: 92%
“…In a model of reperfused feline myocardial infarction, TGF-β1 administration reduced cardiomyocyte death; these protective actions were associated with attenuated neutrophil recruitment in the infarcted myocardium (47). Whether TGF-β-mediated protection in these studies is due to activation of direct pro-survival pathways in cardiomyocytes, or reflects suppression of injurious inflammatory signaling, remains unknown.…”
Section: Effects Of Tgf-β On Ischemic Cardiomyocytesmentioning
confidence: 92%
“…Endogenous TNF-α and IL-1 play as a mediator of inflammatory reactions, whereas, IL-10 and TGF-β have cardioprotective effects on myocardial I/R injury. Previous studies demonstrated that the blocking of pro-inflammatory cytokines or the administration of cardioprotective cytokines reduced infarct size [32][33][34][35][36][37]. On the other hand, the increases in IL-4 and IFN-γ are characteristic of the activation of iNKT cells [9].…”
Section: Myocardial I/r Injury and Cytokinesmentioning
confidence: 99%
“…For example, TGF-fl, increases biosynthesis and release of the vasoconstrictor, endothelin (ET), in vitro (Kurihara et al, 1989;Ohta et al, 1990;Kanse et al, 1991;Endo et a!., 1992). On the basis of this observation, Kurihara et al (1989) suggested that TGF-fl, could be involved in the local regulation of vascular tone by stimulating ET-l release, but Lefer et al (1993) reported that TGF-/I had no haemodynamic effects in vivo. However, the in vitro experiments of Kurihara et al (1989) showed that the increase in ET mRNA was maximal 2h after TGF-fl, stimulation, whereas in the experiments of Lefer et al (1993) haemodynamic effects of TGF-fI were not looked for over several hours in the absence of other interventions.…”
Section: Introductionmentioning
confidence: 99%